Specialised tourism products : development, management and practice - S̆eric, Neven; Milakovic, Ivana Kursan; Peronja, Ivan (Emerald Publishing Limited, 2024)
The author's first experience in creating a unique tourism venture was lighthouse tourism, encapsulated in the Stone Lights project (1999-2001). Through subsequent research and reflections on its commercialization, Specialised Tourism Products: Development, Management and Practice delves into the intricacies and legalities of marketing specialised tourism products. Referencing scientific studies and notable works, they underscore the evolving importance of such offerings for sustainable tourism development. Specialised Tourism Products is a culmination of practical experiences, modelling a systematic approach to tourism development, accentuating the growing significance of specialised tourism content in the wake of climate change and the Covid-19 pandemic. Drawing on their tested projects, the authors present a comprehensive model, sharing their insights with a wider scientific and professional audience, contributing to the ongoing discourse on fostering attractive and competitive destination offerings in the face of contemporary challenges.
Keywords: Tourism -- Management.; Tourism -- Research.; Business & Economics -- Industries -- Hospitality, Travel & Tourism.; Hospitality, sports, leisure and tourism industries.; elektronické knihy; electronic books